Verbal and Non-verbal Representations of Conflict in Speech - Bekaryan, Lilit (Armenian Folia Anglistika, 2005)
The choice of the language means by the interlocuters to express their disposition towards each other, the strategy they apply as well as the use of emotive-expressive and paralinguistic means are of immense importance in conflict interaction (CI). The article attempts to reveal the verbal and non-verbal means that help express conflict in the process of communication. Generalizing the findings of the research three degrees of intensity of conflict interaction have been distinguished – low, mid-level and high.